THE POTENTIAL OF SHRIMP SHELL EXTRACT AND SOURSOP LEAVES AS AN ANTIDIABETES AGENT IN MICE - Tabriz, Shofiyah Azzahro; Hariyatmi, Hariyatmi (Bio-Lectura : Jurnal Pendidikan Biologi, 2025)
Blood glucose levels that remain high over a prolonged period can increase the risk of diseases such as diabetes. Astaxanthin and chitosan from whiteleg shrimp shells and flavonoids from soursop leaves have the potential to lower blood sugar by enhancing insulin sensitivity and inhibiting glucose absorption. This study aimed to assess the potential of shrimp shell extract (SSE) and soursop leaf extract (SLE) as antidiabetic agents in mice. A completely randomized design (CRD) experiment was conducted using 24 male mice (body weight 20-30 g, aged 3-4 months). Twenty mice were induced with hyperglycemia using alloxan at 150 mg/kg body weight, while four mice served as the control. Mice were divided into 6 groups (4 mice each): K1 (control), K2 (Alloxan induction), K3 (SSE 37.5 mg/kg BW), K4 (SSE 42.5 mg/kg BW), K5 (SLE 350 mg/kg BW), K6 (SLE 450 mg/kg BW). Treatments were administered for 14 days, and blood glucose levels were measured on Day 0 and Day 14 using a glucometer strip test. Results showed the highest blood glucose reduction in group K4 (83.81%). Normality and homogeneity tests indicated the data were normal and homogeneous (P>0.05). One-way ANOVA analysis (Fhit α=0.01 > Ftab, 9.53 > 4.25, P<0.01) revealed that SSE and SLE had a very significant effect as antidiabetic agents in lowering mice blood glucose levels. Duncan's post-hoc test confirmed K4 and K6 as the most significant groups. It can be concluded that SSE (42.5 mg/kg BW) and SLE (450 mg/kg BW) are effective in lowering blood glucose levels in mice and hold potential to be developed as antidiabetic agents for managing diabetes mellitus.